Increasing Equitable Access in Public Service: A Descriptive Study About Accessible Materials - Michelle Allgood (Public Administration Review, 2026)
ABSTRACT As the digital footprint of public service expands, the need for accessible materials for individuals with disabilities grows. Public servants must consider accessibility in the creation of all materials, from websites to PDFs to audio and visual media. However, research around accessible material creation in public service has been limited. This study uses data from a 2024 survey of MPA alumni from five universities to identify their familiarity with accessible material creation, including their awareness of their own organization's policies, processes, and training. The findings reveal that respondent awareness of their own organization's practices was correlated with higher familiarity in generating accessible materials. However, many respondents did not know about their organization's practices, identifying the need for increased dialogue about this essential element of social equity and inclusion. As such, suggestions for organizations to improve their practices around accessible material creation along with ideas for continued research are shared.